Originally Posted by

**cameronbb** Hey forum,

This stuff is pretty out-there to me right now. Im sure there'll be a day when it clicks, like snowboarding...but right now im having a tough time. This is in accordance to my csci class...

How do i prove: (in any way youd like)

(p => r)v(q => r)

-r

________

p => -q

and then.. without using the theorem of deduction, give direct proof for:

(p => q) => r

for the 2nd one.. this is what i think i understand.

1. (p => q) => r

2. (-p v q) => r IR

3. -(-p v q) v r IR

4. (p ^ -q) v r DM

5. .....uhhh (-q v r) DL

6. q => r IR